Climate change and Life Expectancy in a Developing Country: Evidence from Greenhouse Gas (CO2) Emission in Nigeria - Amuka, Joseph I.; Asogwa, Fredrick O.; Ugwuanyi, Romanus O.; Omeje, Ambrose N.; Onyechi, Tochukwu (International Journal of Economics and Financial Issues, 2018)
Both natural and human actions have contributed to high greenhouse gas emission and increased concentration of Carbon Dioxide in the atmosphere in the last four decades. This has led to global warming and subsequently to climate change. The adverse effect of climate change on human habitat, food production, human migration and human health can threaten average life span. In this paper, we examined the effect of climate change on life expectancy, with particular reference to greenhouse gas carbon dioxide emission in Nigeria. We adopted linear regression method and used ordinary least square techniques to analyse the data. The data generated from World Bank publications between 1995 and 2013 were quaterized to have enough sample size to permit econometric tests. The coefficient of carbon dioxide emission turned positive indicating possible positive relationship between carbon dioxide greenhouse gas emission and life expectancy. Since it is not statistically significant, it suggests that greenhouse gas (CO2) emission has not reduced the average number of years of Nigerian life. Keywords: climate change, life Expectancy, Greenhouse Gas, CO2 Emission, Nigeria JEL Classification: I12